Perspectives for changes of the legal status of the Polish minority in Germany (Discourse of Law and Administration, 2019)
The article deals with the problem of the status of the Polish population in Germany. The analysis has undergone a way to sign by Germany the Framework Convention for the Protection of National Minorities and the manner established by the legislature of four national minorities, ie. the Frisians, Danes, Roma-Sinti and Sorb. Further investigations concern was currently functioning system and by him created opportunities to raise the status of the Polish minority in Germany, ranging from the need to define the real legal term under which the Poles could represent their own interests.
Keywords: minority; ethnic minority; the Polish minority in Germany; the Framework Convention for the Protection of National Minorities; the Council of Polish Organizations in Germany